Tantangan dan Hambatan Pelaksanaan Supervisi Pendidikan di SMP Darul Falah Jeblog Talun - Linda Puspitasari; Muhammad Husni (Jurnal Wahana Literasi Pendidikan, 2026)
School supervision is very important to help teachers do a better job and improve the overall quality of education. This study aims to find out the problems and difficulties faced when running school supervision at SMP Darul Falah Jeblog Talun. To get the data, the researcher talked directly with the school principal, vice principal, and some teachers, while also observing the school activities and checking their documents. The results show that supervising teachers at SMP Darul Falah isn't always easy. Some of the main problems are that supervisors don't have enough time, teachers don't really understand why they are being supervised, and there is too much paperwork. On top of that, teachers often feel nervous, anxious, or stressed when they are being evaluated because they feel like they are just being judged. These mixed feelings make it hard to create a comfortable learning environment for everyone involved. In conclusion, even though the school supervision plan is already set up well on paper, its actual practice still needs a lot of improvement. Supervisors need more training to do their job better. Most importantly, the school needs to change how it looks at supervision. The focus should shift away from just checking boxes toward working together, talking openly, and genuinely helping teachers grow. By doing this, teachers will feel supported instead of scared, which will eventually make the school a much better place for students to learn every day.